Membangun Keterampilan Literasi Berbasis Character Values Melalui Balinese Folklore Berbantuan Media Call Sebagai Upaya Peningkatan Kemampuan Bahasa Inggris Siswa Kelas V SD N 1 & 2 Paket Agung - Susanti, Luh Meiyana Ariss (Jurnal Pendidikan Bahasa Inggris undiksha, 2019)
In general, this research is aimed at improving the English language skills of grade V SD N 1 & 2 Paket Agung students, especially grades V.A and class V.B, by applying more innovative learning techniques but still prioritizing character values. Specific targets to be achieved are (1) To find out the use of Balinese folklore assisted by CALL media can improve the English literacy skills of grade V students at SD N 1 & 2 Paket Agung Singaraja. (2) To determine the response of teachers and students in using Balinese Folklore assisted by CALL media, it can improve the English literacy skills of grade V students of SD N 1 & 2 Paket Agung Singaraja. This study applies a classroom action research method (CAR) to solve existing problems, where the average score obtained for students' skills in expressing themselves in reading activities in the first cycle is: 66.56. From these scores, it is classically found that the mean score for class V.A is 67.34 and for class V.B is: 65.78. While there was an increase in cycle II where the average score of students was: 76.17, it was classically found that the average score for class V.A was 77.34 and in class V.B was: 75.00. In terms of writing skills, the average score obtained by students also increased. The results obtained were not much different from the results on reading skills.